2018
DOI: 10.1371/journal.pone.0194915
|View full text |Cite|
|
Sign up to set email alerts
|

Improvement of the reduction in catastrophic health expenditure in China’s public health insurance

Abstract: This study aimed to locate the contributing factors of Catastrophic Health Expenditure (CHE), evaluate their impacts, and try to propose strategies for reducing the possibilities of CHE in the context of China’s current public health insurance system. The financial data of all hospitalization cases from a sample hospital in 2013 were gathered and used to determine the pattern of household medical costs. A simulation model was constructed based on China’s current public health insurance system to evaluate the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 43 publications
(41 reference statements)
1
21
0
Order By: Relevance
“…As for the indicator of catastrophic health expenditure, recent national studies showed that China made progress in reducing the rate of catastrophic health expenditure, especially for low-income groups 7 8. However, the financial burden for medical services of patients remains high 9 10…”
Section: Financial Protectionmentioning
confidence: 99%
“…As for the indicator of catastrophic health expenditure, recent national studies showed that China made progress in reducing the rate of catastrophic health expenditure, especially for low-income groups 7 8. However, the financial burden for medical services of patients remains high 9 10…”
Section: Financial Protectionmentioning
confidence: 99%
“…The World Health Organization (WHO) proposed that CHE occurs when health care payments equal or exceed 40% of a household's non-subsistence income [12]. Indeed, residents in China are faced with higher economic burden of diseases, and the overall incidence of CHE is about 13%, while the incidence of CHE can be more than 50% for low-income rural families [13,14].…”
mentioning
confidence: 99%
“…First, we observed the incidence and intensity of CHE rose over the study period with two measurement standards. The previous study had reported that the possibility of CHE could be higher than 50% of lowincome rural households in China [18]. This was unexpected because many policies were adopted in this period for reducing the level of CHE.…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, the determinants of CHE have been extensively explored by previous studies. Household economic status, the inpatient rate, presence of an elderly or disabled household member, and the presence of a household member with chronic illness were commonly associated with CHE [16][17][18]. While it was thought that health insurance would help to alleviate some of the economic burden brought about by disease, the evidence has remained unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation